Midazolam as A Sedative Agent in Paediatric Dentistry- A Literature Review - Neethu Ann Preethy1 , Sujatha Somasundaram2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Behaviour management forms an integral part of managing children in the day to day paediatric dentalpractice. Pharmacological behaviour management strategies serve to be an effective alternative whenthe basic behaviour management technique fails. Pharmacological management strategies involve theadministration of general anaesthesia or sedation. Recently, midazolam has gained popularity for use inconscious sedation in paediatric dentistry. Midazolam has a short half-life, which results in rapid onset andrecovery in paediatric dental patients, hence encouraging its use in paediatric dentistry